2017
DOI: 10.1007/s12046-017-0656-2
|View full text |Cite
|
Sign up to set email alerts
|

Impedance estimation of photovoltaic modules for inverter start-up analysis

Abstract: Starting-up of photovoltaic (PV) inverters involves pre-charging of the input dc bus capacitance. Ideally, direct pre-charging of this capacitance from the PV modules is possible as the PV modules are current limited. Practically, the parasitic elements of the system such as the PV module capacitance, effective wire inductance and resistance determine the start-up transient. The start-up transient is also affected by the contactor connecting the PV modules to the inverter input dc bus. In this work, the start-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Focusing on low irradiation conditions (about 100 W/m 2 ), reference [42] describes that the parallel capacitance at MPP and OC conditions could achieve a 294% and 340% value, respectively, compared to that of the SC condition. The resulting parallel capacitance is also irradiance-dependent [42,46,51,59,60]. Thus, for different voltage biases, this capacitance could decrease in the range 15% to 70% when irradiance decreases from high to low irradiation [42,60].…”
Section: Dynamic and Insulation Model Of A Pv Modulementioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on low irradiation conditions (about 100 W/m 2 ), reference [42] describes that the parallel capacitance at MPP and OC conditions could achieve a 294% and 340% value, respectively, compared to that of the SC condition. The resulting parallel capacitance is also irradiance-dependent [42,46,51,59,60]. Thus, for different voltage biases, this capacitance could decrease in the range 15% to 70% when irradiance decreases from high to low irradiation [42,60].…”
Section: Dynamic and Insulation Model Of A Pv Modulementioning
confidence: 99%
“…Modelling and value setting of dynamic AC circuit parameters for a PV module gives important insight to characterize and diagnose its behavior in case of lightning events. Extensive studies on the determination of parameters of the active electrical circuitry for PV cells and modules are available in the literature, mostly focused on calculating both the DC and AC electrical parameters [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. The most widely used method to study the PV dynamic behavior is the impedance spectroscopy [40,43,[54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the analysis and design of such systems, a proper dynamic model of the multi-string PV system is to be used. Several attempts have been made to obtain dynamic models of a PV module [35][36][37][38][39][40][41]. However, in this research work, the dynamic model parameters of the roof-mounted multistring PV system shown in Figure 2 were obtained from a set of experimental data.…”
Section: Dynamic Model Of Multi-string Pv Systemmentioning
confidence: 99%
“…These SMPC systems are promising to be one of the best methods of characterizing PV arrays owing to their controllable and fast response, designed ability to handle high power and optional power conditioning capability [29]. These converters are further useful in transient characterization of PV panels for dynamic modeling [38] and can therefore be instrumental in fault diagnosis. SMPC systems also work well in fast changing environmental conditions wherein special cautions such as high characterization speeds are needed when irradiation changes fast [26].…”
Section: Introductionmentioning
confidence: 99%